OPTIMISASI EKONOMI PENGELOLAAN SUMBERDANA PERIKANAN UDANG - Purwanto Purwanto; Kamiso H Nitimulyo; Tumari Jatileksono (Agro Ekonomi, 1990)
This paper presents the economic optimization of the shrimps fishing industry in the south coast of Central Java and adjacent waters. The physical yield function of the shrimps fishery is incorporated in an economic model to analyze the relationship between the level of fishing effort and the economic efficiency of the fishery. The open access fishery and the controlled fishery at maximum sustainable yield level causes inefficient allocation of resources. Only through control the effort at the level where marginal oost of production equal price resources can be allocated efficiently. The government intervention is necessary to restrict fishing effort to a level that would be economically optimum